Structural Characterization and Anti-inflammatory Activity of a Galactorhamnan Polysaccharide From Citrus medica L. var. sarcodactylis - Luo, Bi; Lv, Jia; Li, Kejie; Liao, Peiran; Chen, Peng (Frontiers in Nutrition, 2022)
This study aimed to extract polysaccharides from Citrus medica L. var. sarcodactylis (finger citron fruits) and analyze their structures and potential bioactivities. A new polysaccharide named K-CMLP was isolated and purified by Diethylaminoethylcellulose (DEAE)-Sepharose Fast Flow and DEAE-52 cellulose column chromatography with an average molecular weight of 3.76 × 103 kDa. Monosaccharide composition analysis revealed that K-CLMP consisted of rhamnose, galactose, and glucose, with a molar ratio of 6.75:5.87:1.00. Co-resolved by methylation and two-dimensional nuclear magnetic resonance (NMR), K-CLMP was alternately connected with 1, 2-Rha and 1, 4-Gal to form the backbone, and a small number of glucose residues was connected to O-4 of rhamnose. The results of DPPH⋅ and ABTS+⋅ radical scavenging assays indicated that both crude polysaccharide Citrus medica L. var. polysaccharide (CMLP) and K-CLMP exhibited strong free-radical-scavenging properties in a dose-dependent manner. In addition, K-CMLP significantly inhibited the production of pro-inflammatory cytokines (IL-6 and TNF-α) and reactive oxygen species (ROS) in RAW 264.7 cells treated with LPS. These results provide a basis for further use as one of the potential functions of food or natural medicine.